2016
DOI: 10.1007/s00167-016-4148-4
|View full text |Cite
|
Sign up to set email alerts
|

Rotator cuff tendon connections with the rotator cable

Abstract: The connection between the rotator cable and rotator cuff tendons is tight and confirms the suspension bridge theory for rotator cuff tears in most areas between the SSP tendons and rotator cable. In its posterior insertion area, the rotator cable is a connecting structure between the TM, ISP and SSP tendons. These findings might explain why some patients with relatively large rotator cuff tears can maintain seamless shoulder function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 8 publications
3
27
0
Order By: Relevance
“…Embryological studies report only that the development of the glenohumeral joint capsule occurs during Carnegie stages 22–23 (Aboul-Mahasen and Sadek 2002; Fealy et al 2000; Hita-Contreras et al 2017). However, as it has been reported in macroscopic (Burkhart et al 1993; Rahu et al 2016) and microscopic (Fallon et al 2002) studies, and as we confirmed in normal and pathological specimens, rotator cables form a functional complex with the supra- and infraspinatus muscles. Moreover, our dimensions of the cables were comparable with data from the recent MRI (Gyftopoulos et al 2013) and ultrasound (Orlandi et al 2012; Sconfienza et al 2012) studies where only the dimensions of the cable, not the complex with the spinatus tendons, were analysed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Embryological studies report only that the development of the glenohumeral joint capsule occurs during Carnegie stages 22–23 (Aboul-Mahasen and Sadek 2002; Fealy et al 2000; Hita-Contreras et al 2017). However, as it has been reported in macroscopic (Burkhart et al 1993; Rahu et al 2016) and microscopic (Fallon et al 2002) studies, and as we confirmed in normal and pathological specimens, rotator cables form a functional complex with the supra- and infraspinatus muscles. Moreover, our dimensions of the cables were comparable with data from the recent MRI (Gyftopoulos et al 2013) and ultrasound (Orlandi et al 2012; Sconfienza et al 2012) studies where only the dimensions of the cable, not the complex with the spinatus tendons, were analysed.…”
Section: Discussionsupporting
confidence: 89%
“…Others have described it as the “circular fibres system” (Gohlke et al 1994 ) or the “transverse band” (Clark and Harryman 1992 ). Despite the varying nomenclature, it is uniformly known to be part of a functional complex with spinatus muscles (Rahu et al 2016 ) and plays a role similar to a cable of a suspension bridge. Thus, according to Burkhart et al ( 1993 ) it transfers the forces of supra- and infraspinatus muscles to the humerus in particular cases of rotator cuff tears.…”
Section: Introductionmentioning
confidence: 99%
“…Arthroscopic studies as well as recent anatomic articles have provided detailed descriptions of the superior glenohumeral joint capsule. Burkhart et al 4 and Kolts et al 15 described the rotator cable in the superior part of the glenohumeral joint with the anatomic term “ligamentum semicirculare humeri.” In an anatomic study, Rahu et al 24 found that the superior capsuloligamentous structures were tightly connected to the supraspinatus tendon and could be considered the insertion area for this tendon. In the posterior insertion area, the rotator cable connects the teres minor, infraspinatus, and supraspinatus tendons.…”
Section: Discussionmentioning
confidence: 99%
“…Among such cases, the most commonly affected tendon is the supraspinatus tendon. 10,11,15,16 Typically, more than 80% of cases of total calcific tendinitis in the rotator cuff region occur in the supraspinatus tendon. These data are consistent with findings obtained by Louwerens et al for both asymptomatic and symptomatic groups, which indicated that only 10% of all calcification deposits were found in the infraspinatus tendon, and no cases of calcific tendonitis in the teres minor region have been reported in the PubMed.…”
Section: Discussionmentioning
confidence: 99%